Does aquatic exercise reduce hip and knee joint loading? In vivo load measurements with instrumented implants - Kutzner, Ines; Richter, Anja; Gordt, Katharina; Dymke, Jörn; Damm, Philipp; Duda, Georg N.; Günzl, Reiner; Bergmann, Georg (PloS one, 2017)
Aquatic exercises are widely used for rehabilitation or preventive therapies in order to enable mobilization and muscle strengthening while minimizing joint loading of the lower limb. The load reducing effect of water due to buoyancy is a main advantage compared to exercises on land. However, also drag forces have to be considered that act opposite to the relative motion of the body segments and require higher muscle activity. Due to these opposing effects on joint loading, the load-reducing effect during aquatic exercises remains unknown. The aim of this study was to quantify the joint loads during various aquatic exercises and to determine the load reducing effect of water. Instrumented knee and hip implants with telemetric data transfer were used to measure the resultant joint contact forces in 12 elderly subjects (6x hip, 6x knee) in vivo. Different dynamic, weight-bearing and non-weight-bearing activities were performed by the subjects on land and in chest-high water. Non-weight-bearing hip and knee flexion/extension was performed at different velocities and with additional Aquafins. Joint forces during aquatic exercises ranged between 32 and 396% body weight (BW). Highest forces occurred during dynamic activities, followed by weight-bearing and slow non-weight-bearing activities. Compared to the same activities on land, joint forces were reduced by 36-55% in water with absolute reductions being greater than 100%BW during weight-bearing and dynamic activities. During non-weight-bearing activities, high movement velocities and additional Aquafins increased the joint forces by up to 59% and resulted in joint forces of up to 301%BW. This study confirms the load reducing effect of water during weight-bearing and dynamic exercises. Nevertheless, high drag forces result in increased joint contact forces and indicate greater muscle activity. By the choice of activity, movement velocity and additional resistive devices joint forces can be modulated individually in the course of rehabilitation or preventive therapies.